If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 + -5 = 12 Reorder the terms: 1 + -5 + 4x = 12 Combine like terms: 1 + -5 = -4 -4 + 4x = 12 Solving -4 + 4x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 12 + 4 4x = 12 + 4 Combine like terms: 12 + 4 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| x^2=3x+5 | | 12y-5=2 | | 4a+4=8 | | 3x^2+17x-6= | | 3x^2+17-6= | | 2X+35-15=20 | | 49-64x^2=0 | | 5n+25g=5.65 | | -7x-3y-2+7x= | | x+5y=57 | | x+5y= 57 | | -3x+4y=76 | | -6b+13b= | | 12b+3+2=20 | | n=2(l+w)-4 | | 3-(Inj(1))=3a | | 9c+7=21 | | 5x^6-125X^4=0 | | 7y=4y+8 | | 3-In(1)=3a | | -(-4)= | | 12a-7=15 | | 4y=7y+8 | | 8i+4=10 | | -5x-3x+x= | | 14x-2(x-9)+21= | | 3(2x-2)-2(3x+4)= | | 3-3u=4-2u | | 4(a+9)-12= | | 5+2*(2x-4)= | | x^3-100x=0 | | 2-(5-x)+3(-2x)= |